EDUKASI PIJET ENDROPHIN UNTUK MENGURANGI NYERI PERSALINAN - Wahyuni, Iin; Utaminingtyas, Farida; Aditia, Dita Selvia; Muri, Putri Hilwati (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2024)
Pain arises as a result of psychological responses and physical reflexes. According to (Maryunani, 2010), the pain felt during the first stage of labor is painful and uncomfortable in the acceleration phase, the pain is felt to be somewhat sharp in the maximum dilation phase, and the pain becomes more intense, piercing and stiff in the deceleration phase. One way of non-pharmacological management to reduce labor pain is with endorphine massage. Endorphin Massage is a light touch/massage therapy that is quite important to give to pregnant women, in the time leading up to giving birth. This is because massage stimulates the body to release endorphin compounds which are pain relievers and can create feelings of comfort. So far, endorphins have been known as substances that have many benefits (Kuswandi, 2011). The methods used were lectures, questions and answers and endorphin massage demonstrations. The materials used are counseling materials and endorphin massage. There were 15 participants in the activities for pregnant women at the Surya Medika Clinic. There were enthusiastic participants when the activity took place. Participants know the benefits of endhorphin massage. Pregnant women need to get good and correct IEC endhorphin massage so they can implement healthy living habits.